Use of the triple coaxial (triaxial) microcatheter system in superselective arterial embolisation for complex interventional cases: an initial experience with the system - Sonam Tashi; Zehao Tan; Apoorva Gogna (CVIR Endovascular, 2022)
Abstract Learning objective To share our experience in utilising the triple coaxial (triaxial) system in superselective cannulation of arteries for complex embolisation procedures. Background Percutaneous transcatheter selective embolisation is widely performed for a myriad of oncologic (e.g., trans-arterial chemo- or radio-embolisation) and non-oncologic (e.g., for embolisation of bleeding and benign conditions such as uterine fibroid and benign prostate hyperplasia) purposes. The cornerstone of such embolisation procedures is to achieve superselective cannulation of the arterial supply to the tumour/organ, preventing the complication of non-target embolisation. However, a multitude of factors, such as complex vascular anatomy, can pose challenges to achieving this goal. Clinical findings/procedural details The triaxial system utilises two smaller microcatheters telescoped through each other over a microwire. We have adopted the triaxial system for specific cases due to its perceived superior torquability and trackability compared to the conventional coaxial system, in which superselective cannulation is anticipated to be challenging. The triaxial system is also favourable in situations where the inner microcatheter needs to be “sacrificed” after administering the embolics (e.g., after administering radioisotopes in radioembolisation, N-butyl cyanoacrylate [NBCA] glue or ethylene–vinyl alcohol copolymer [EvOH] Onyx). Through a case series with procedural details such as fluoroscopic time, contrast administered, etc., we hope to illustrate the utility and efficacy of the triaxial system as well as present pitfalls in its usage. Conclusion The triaxial system appears to be a valuable system for certain complex embolisation procedures and could be better suited than the conventional coaxial systems in these specific circumstances.